Effects of land use on soil degradation in Giriwoyo, Wonogiri, Indonesia - Mujiyo Mujiyo; Tiara Hardian; Hery Widijanto; Aktavia Herawati (Brawijaya University, 2021)
This study aimed at determining the effect of land use on soil degradation, discovering the indicator as a determinant factor of soil degradation, and providing recommendations for land management to improve soil productivity. This study was conducted in agricultural lands in Giriwoyo, Wonogiri, Indonesia, and the observation indicator adopted by the Indonesian Government Regulation concerning Soil Degradation Control for Biomass Production. The methodology used was survey research with purposive sampling points in 12 land mapping units, and each unit was represented three times. The result showed that the study area was slightly and moderately degraded. Land use significantly affected soil degradation, and the paddy field has the highest degradation in the study area. Soil characteristics as degradation factors in the study area were soil texture, bulk density, and total porosity. Strategy for land management can be made by limiting the use of chemical fertilizers, and changing the use of chemical fertilizers into compost, to increase soil organic content, and accelerate the availability of nutrients.